Genomic variations and susceptibility to sepsis - Papathanassoglou, Elizabeth; Giannakopoulou, Margarita; Bozas, Evangelos (My University, 2006)
The considerable variability in septic patients' outcomes, which exceeds our understanding of the pathophysiology of sepsis and defies our current prognostic tools, has prompted investigation in the genetic variations that may predispose individuals for increased susceptibility to sepsis and adverse outcomes. This article aims to critically review current evidence from genetic association studies regarding the role of genetic polymorphisms in sepsis. Findings regarding polymorphisms in intercellular messenger mediators (cytokines), membrane-bound inflammatory receptors, intracellular signaling cascades, heat shock proteins, coagulation/fibrinolysis pathways, apoptotic mechanisms, and neuroendocrine axes are presented and discussed. Study results are often discrepant, whereas many methodological limitations, in terms of both study design and genotyping methods, may render the results difficult to generalize. Nonetheless, a role for genomic variations in sepsis outcomes has emerged. A theoretical framework for incorporation of genetic variations into individualized care planning based on complexity theory is proposed, and future prospects of microarray technology and systems modelling are discussed briefly
Keywords: Critical care nursing; Septicemia; Coagulation; Cytokines; Blood coagulation factors; Biological models